Presence of subclinical giant cell arteritis in patients with morning stiffness of duration less than 45 minutes at the time of diagnosis of polymyalgia rheumatica - Ciro Manzo; Alberto Castagna; Nicola Veronese; Marco Isetta (Rheumatology, 2024)
Introduction In some patients with polymyalgia rheumatica (PMR), giant cell arteritis (GCA) is subclinical as under-lying inflammation of large vessels (LV) is present without evidence of related clinical manifestations. Different factors have been proposed as predictive of subclinical GCA in PMR patients. To date, the literature reports scant data about the association between subclinical GCA and long-lasting morning stiffness (MS) in patients at the time of diagnosis of PMR. Given this background, the aim of this study was to assess the association between subclinical GCA and MS < 45 min in patients with newly diagnosed PMR.